Human Gut-Commensalic Lactobacillus ruminis ATCC 25644 Displays Sortase-Assembled Surface Piliation: Phenotypic Characterization of Its Fimbrial Operon through In Silico Predictive Analysis and Recombinant Expression in Lactococcus lactis. - Xia Yu; Annukka Jaatinen; Johanna Rintahaka; Ulla Hynönen; Outi Lyytinen; Ravi Kant; Silja Åvall-Jääskeläinen; Ingemar von Ossowski; Airi Palva (PLoS ONE)
Sortase-dependent surface pili (or fimbriae) in Gram-positive bacteria are well documented as a key virulence factor for certain harmful opportunistic pathogens. However, it is only recently known that these multi-subunit protein appendages are also belonging to the "friendly" commensals and now, with this new perspective, they have come to be categorized as a niche-adaptation factor as well. In this regard, it was shown earlier that sortase-assembled piliation is a native fixture of two human intestinal commensalics (i.e., Lactobacillus rhamnosus and Bifidobacterium bifidum), and correspondingly where the pili involved have a significant role in cellular adhesion and immunomodulation processes. We now reveal that intestinal indigenous (or autochthonous) Lactobacillus ruminis is another surface-piliated commensal lactobacillar species. Heeding to in silico expectations, the predicted loci for the LrpCBA-called pili are organized tandemly in the L. ruminis genome as a canonical fimbrial operon, which then encodes for three pilin-proteins and a single C-type sortase enzyme. Through electron microscopic means, we showed that these pilus formations are a surface assemblage of tip, basal, and backbone pilin subunits (respectively named LrpC, LrpB, and LrpA) in L. ruminis, and also when expressed recombinantly in Lactococcus lactis. As well, by using the recombinant-piliated lactococci, we could define certain ecologically relevant phenotypic traits, such as the ability to adhere to extracellular matrix proteins and gut epithelial cells, but also to effectuate an induced dampening on Toll-like receptor 2 signaling and interleukin-8 responsiveness in immune-related cells. Within the context of the intestinal microcosm, by wielding such niche-advantageous cell-surface properties the LrpCBA pilus would undoubtedly have a requisite functional role in the colonization dynamics of L. ruminis indigeneity. Our study provides only the second description of a native-piliated Lactobacillus species, but at the same time also involves the structural and functional characterization of a third type of lactobacillar pilus.